Green technology : green glycosylation promoted by reusable biomass carbonaceous solid acid - Meigi, Soesanto (2013)
Glycosylation is the enzymatic process that attaches glycans to proteins, lipids or other organic molecules. It provides a unique platform to synthesize an array of carbohydrate-derived novel therapeutic agents1 and plays a significant role in food and cosmetic industries. Previously, the promoters used for this reaction were Lewis acid catalysts. Nowadays, solid acid catalysts have become more prominent because of no work-up procedures, easy separation, recovery and reusability. Hence, we wish to report glycosylation reactions promoted by sulfonated biomass carbonaceous material. [4th Award]